Solubility modulation of polyfluorene emitters by thermally induced (retro)-Diels-Alder cross-linking of cyclopentadienyl substituents - Ahrens, Lukas; Schlißke, Stefan; Strunk, Karl-Philipp; Hinkel, Felix Peter; Melzer, Christian; Bunz, Uwe H. F.; Lemmer, Uli; Hernandez-Sosa, Gerardo; Jänsch, Daniel; Freudenberg, Jan; Müllen, Klaus (Chemistry of materials, 2018)
For cost-efficient organic electronic devices, the consecutive deposition of active layers by solution-based processes is a key benefit. We report a synthetic approach enabling solubility reduction of bis(cyclopentadienyl)-substituted polyfluorenes as emissive layers in organic light-emitting diodes (OLEDs). Thermally induced retro-Diels-Alder reaction liberates free cyclopentadiene as “protecting group” and pending cyclopentadienyl units, which cross-link the polymer strands upon cooling via [4+2] cycloadditions. The activation temperature is tuned in the range of 180-250 °C through alkyl, alkoxy, or ester linkages. Ultimately, macrocyclic self-protected bis(cyclopentadienylene) moieties avoid extrusion of volatile cyclopentadiene during activation. The solvent resistance of the emissive layers after cross-linking is examined by absorption spectroscopy and white light scanning interferometry. The influence of the desolubilization procedure on the performance of solution-processed OLEDs is investigated.